Perancangan Concept Art Karakter “Arjuna” Pada Film Animasi 3d “Mahabarata” - Hendri Bastian (Peneliti.net, 2023)
Concept art is a form of art that is widely used in the entertainment industry such as animation,comics, games and visual novels, in this case the researcher will discuss about animated films,designing concepts in films requires a research in accordance with the theme to be raised, researchcan be verbal which is then processed and transformed into visual form, Concept art plays animportant role in the transformation process, Concept art is processed using creativity based ondata based on verbal or visual research, This research is a creative process in designing Conceptart on animation with the theme of puppetry, it is expected to be one of the guidelines in theproduction process of animated films and researchers hope that this will be one of the solutions toovercome the problem of how to transform puppets into a more unique, attractive form, acceptableto the public and has relevant modern elements.